Creating a Teacher Development Program Linked to Curriculum Renewal (2018)
This paper presents one Colombian university English as a foreign language program’s in-house teacher development program for curriculum renewal. This program is an innovative attempt to prepare teachers for implementing a new curriculum and, simultaneously, engages them in professional development activities. The program is a response to the lack of existing teacher and professional development models that fit certain specific contextual needs, including preparation for implementing new curriculum as well as emphases in the updating of particular teaching practices. In addition to presenting the program, the article also describes the integration of key aspects of various existing models of teacher and professional development into one program that meets contextual needs while encouraging positive change among faculty and students.